Reducing Red Tape to Strengthen Teachers’ Organizational Citizenship Behavior in Boalemo Local-Wisdom Elementary Schools - Dwi Indah Yuliani Solihin; Asna Aneta; Heldi Vanni Alam; Novianty Djafri (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to strengthen teachers’ Organizational Citizenship Behavior (OCB) by reducing local bureaucratic red tape and developing a creative-adaptive elementary school ecosystem grounded in Boalemo local wisdom. Using Participatory Action Research combined with Asset-Based Community Development at SD Negeri 3 Tilamuta, Boalemo Regency, the study involved 25 grade 4–6 teachers, one principal, and three district education office staff. Data were collected through focus group discussions, OCB and red tape questionnaires, field observation, module document review, and photographic documentation. The intervention comprised four stages: red tape diagnosis, OCB and bureaucracy-literacy workshops, mentoring for Ayambo local-wisdom modules using project-based learning, and policy blueprint validation. Six red tape points were identified. Teachers’ mean OCB score increased from 3.21 to 4.22, five Ayambo-based learning modules were produced with accompanying lesson plans, worksheets, and assessment rubrics, and a school bureaucracy simplification blueprint was validated with the district education office. This study uniquely integrates red tape reduction, OCB strengthening, and culturally responsive school-based management within a single participatory framework. The model offers a replicable intervention for enhancing teacher engagement and streamlining administrative processes in other elementary schools. This research contributes actionable evidence that combining local wisdom with participatory capacity-building effectively reduces bureaucratic burdens and elevates teachers’ discretionary efforts, providing a contextualized blueprint for sustainable school transformation in similar rural settings.